2022
DOI: 10.3389/fphys.2022.1059221
|View full text |Cite
|
Sign up to set email alerts
|

Running economy and lower extremity stiffness in endurance runners: A systematic review and meta-analysis

Abstract: Background: Lower extremity stiffness simulates the response of the lower extremity to landing in running. However, its relationship with running economy (RE) remains unclear. This study aims to explore the relationship between lower extremity stiffness and RE.Methods: This study utilized articles from the Web of Science, PubMed, and Scopus discussing the relationships between RE and indicators of lower extremity stiffness, namely vertical stiffness, leg stiffness, and joint stiffness. Methodological quality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…A greater RFD after HL interventions would allow athletes to generate higher levels of force in short periods of time, allowing a rapid transition from the braking phase to the propulsion phase of the gait cycle, promoting favourable muscular conditions [ 123 ] that maximise the force–velocity relationship [ 125 ] and, thus, RE. On the other hand, HL may improve RE due to changes in lower limb stiffness [ 123 , 126 , 127 ], which would result in more efficient energy storage and release from the lower limbs, thus reducing the energy cost of running [ 128 ]. For example, a study by Millet et al [ 103 ] reported significant increases in RE after 14 weeks of HL and this was accompanied by an increase in leg stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater RFD after HL interventions would allow athletes to generate higher levels of force in short periods of time, allowing a rapid transition from the braking phase to the propulsion phase of the gait cycle, promoting favourable muscular conditions [ 123 ] that maximise the force–velocity relationship [ 125 ] and, thus, RE. On the other hand, HL may improve RE due to changes in lower limb stiffness [ 123 , 126 , 127 ], which would result in more efficient energy storage and release from the lower limbs, thus reducing the energy cost of running [ 128 ]. For example, a study by Millet et al [ 103 ] reported significant increases in RE after 14 weeks of HL and this was accompanied by an increase in leg stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…8 ). Indeed, it has been observed that the correlation between leg stiffness and RE increases with V O 2 max [ 127 ]. Given that more highly trained athletes make more efficient use of elastic energy (i.e., the Achilles tendon) to minimise muscle energy cost [ 140 ], coupled with a possible increase in tendon stiffness generated by HL [ 133 ], it is possible that athletes with higher levels of performance (i.e., higher initial V O 2 max) may be better able to transfer these adaptations to running at a lower energy cost.…”
Section: Discussionmentioning
confidence: 99%